2023
DOI: 10.1002/hpm.3619
|View full text |Cite
|
Sign up to set email alerts
|

How context influences the functionality of community‐level health governance structures: A case study of community health committees in Kenya

Abstract: Community Health Committees (CHCs) are mechanisms through which communities participate in the governance and oversight of community health services. While there is renewed interest in strengthening community participation in the governance of community health services, there is limited evidence on how context influences community‐level structures of governance and oversight. The objective of this study was to examine how contextual factors influence the functionality of CHCs in Kajiado, Migori, and Nairobi Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Our research has identified interrelated issues among three actors that may negatively affect service quality: (a) deficiencies in active CHWs; (b) a lack of support from Puskesmas; and (c) a lack of leadership among village heads. We consider the concept of governance to be a crucial element in PHC systems, represented by Puskesmas and official community administrators [ 23 , 24 ]. This indicates that systems thinking and strengthening frameworks help us capture the roles of Puskesmas and village heads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research has identified interrelated issues among three actors that may negatively affect service quality: (a) deficiencies in active CHWs; (b) a lack of support from Puskesmas; and (c) a lack of leadership among village heads. We consider the concept of governance to be a crucial element in PHC systems, represented by Puskesmas and official community administrators [ 23 , 24 ]. This indicates that systems thinking and strengthening frameworks help us capture the roles of Puskesmas and village heads.…”
Section: Discussionmentioning
confidence: 99%
“…The examination of village governance also underscores the importance of establishing village committees composed of community representatives [ 24 , 28 , 29 ]. These committees, which typically include community members, public health center staff, and volunteer organization representatives, play a crucial role in decision-making about village affairs, overseeing community health service delivery, and supporting volunteer workers.…”
Section: Discussionmentioning
confidence: 99%
“…Mainstream cultural identity is composed of two factors: public participation and mainstream culture, and national cultural identity is composed of four factors: tolerance, ethnic preference, Ethnic connotation, and religious belief. This study used a questionnaire to conduct an empirical survey on the cultural identity of college students (Karuga et al,2023). Cultural assertiveness is the perception of the culture of the group where people live.…”
Section: The Relationship Between Cultural Identity and Cultural Self...mentioning
confidence: 99%